2016
DOI: 10.1007/s00394-016-1273-2
|View full text |Cite
|
Sign up to set email alerts
|

Monoterpene phenolic compound thymol promotes browning of 3T3-L1 adipocytes

Abstract: Our findings suggest that 3T3-L1 is a potential cell model for screening browning agents. Thymol plays multiple modulatory roles in the form of inducing the brown-like phenotype as well as enhancing lipid metabolism. Thus, thymol may be explored as a potentially promising food additive for prevention of obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 43 publications
0
41
0
1
Order By: Relevance
“…confirmed that phytol (acyclic diterpene) increases the number of adipocytes and prevent obesity. Moreover , many investigators suggested that a dietary monoterpene phenolic compound of thymol and monoterpene of limonene plays a role in the browning of white adipocytes, augmentation of lipolysis, fat oxidation, and thermogenesis …”
Section: Discussionmentioning
confidence: 99%
“…confirmed that phytol (acyclic diterpene) increases the number of adipocytes and prevent obesity. Moreover , many investigators suggested that a dietary monoterpene phenolic compound of thymol and monoterpene of limonene plays a role in the browning of white adipocytes, augmentation of lipolysis, fat oxidation, and thermogenesis …”
Section: Discussionmentioning
confidence: 99%
“…Findings have been consistent with each other, indicating that THY supplementation leads to a big increase in antioxidant enzyme activity involving glutathione peroxidase and superoxide dismutase and a decrease in malondialdehyde levels, associated with a greater concentration of PUFA precursors such as linoleic acid and α ‐linolenic acid as well as LC derivatives such as arachidonic acid and docosahexaenoic acid, as observed herein. Additionally, in vitro and in vivo studies have demonstrated that THY as well as EOs with THY supplementation may alter several lipid metabolic pathways, including bile acid, cholesterol synthesis and fatty acid metabolism, indicating that THY plays multiple modulatory roles in lipid metabolism . One of the mechanisms by which supplementation with THY or EOs containing THY would reflect an increase in the antioxidant capacity/status of supplemented females is based on its inhibitory effect on lipogenesis and its hypolipidemic actions .…”
Section: Discussionmentioning
confidence: 99%
“…Thymol promotes the expressions of brown fat-specific markers including PPARγ via activation of AMPK signalling [37]. Pretreatment with AMPK agonist AICAR significantly prevented the increased TLR4 protein expressions (Fig.…”
Section: Resultsmentioning
confidence: 99%